Robust and tissue-independent gender-specific transcript biomarkers. (8th July 2013) - Staedtler, Frank; Hartmann, Nicole; Letzkus, Martin; Bongiovanni, Sandrine; Scherer, Andreas; Marc, Philippe; Johnson, Keith J.; Schumacher, Martin M.
Abstract: Context : Correct gender assignment in humans at the molecular level is crucial in many scientific disciplines and applied areas. Materials and methods : Candidate gender markers were identified through supervised statistical analysis of genome wide microarray expression data from human blood samples ( N  = 123, 58 female, 65 male) as a training set. The potential of the markers to predict undisclosed tissue donor gender was tested on microarray data from 13 healthy and 11 cancerous human tissue collections (internal) and external datasets from samples of varying tissue origin. The abundance of some genes in the marker panel was quantified by RT-PCR as alternative analytical technology. Results : We identified and qualified predictive, gender-specific transcript markers based on a set of five genes (RPS4Y1, EIF1AY, DDX3Y, KDM5D and XIST). Conclusion : Gene expression marker panels can be used as a robust tissue- and platform-independent predictive approach for gender determination.